The main challenges of small beginning entrepreneurs in the front of global competitiveness - Silva , Édi Mário Ferreira da; Costa , Elvio Carlos da; Vitalli , Yuri Mateus (Seven Editora, 2023)
The study provides important information for budding entrepreneurs facing challenges in the highly competitive global landscape. Faced with this fierce competitiveness, entrepreneurs are required to adopt effective strategies so that they can stand out and ensure their survival and success. The general objective was to analyze the main challenges faced by small beginning entrepreneurs in the face of global competitiveness. To this end, the specific objectives are: 1) raise and present possible solutions to the main obstacles faced by small beginning entrepreneurs; and 2) verify and contextualize the different possibilities of stabilizing yourself in the current market and ensuring the success of your venture. Methodologically, the present study was carried out through a bibliographical search in a database recognized in academic and scientific circles, in addition to field research, through the application of a semi-structured questionnaire containing 15 open and closed questions, related to the proposed main theme. . The questionnaire was answered by 11 participants, all of whom are entrepreneurs who are starting out and looking to establish themselves in the current market. The results indicate that one of the most common strategies among participating entrepreneurs is attracting customers, with the combination of competitive prices, quality products and speed of delivery. Furthermore, promotions are widely used to attract and retain customers, demonstrating the importance of marketing and attractive pricing strategies for the success of businesses. Regarding short and long-term goals, many entrepreneurs seek stability and visibility in the market. This quest for establishment is understandable, as global competition requires companies to build a solid foundation to survive and grow. Thus, it can be concluded that research should possibly contribute to the growth of beginning entrepreneurs and, consequently, to economic development and social inclusion in a competitive global environment. DOI:https://doi.org/10.56238/interdiinovationscrese-068